COMPUTAÇÃO QUÂNTICA EM QUÍMICA - Caio M. Porto; Matheus S. Fonseca; Guilherme de S. T. Morais; Celso J. Villas-Boas; Rene A. Nome; Nelson H. Morgon (Química Nova)
QUANTUM COMPUTING IN CHEMISTRY. Quantum computing offers transformative potential for quantum chemistry, enabling the exploration of complex molecular simulations with unprecedented accuracy. By leveraging qubits and powerful quantum algorithms like the variational quantum eigensolver (VQE) and quantum phase estimation (QPE), quantum computing provides a novel approach to unraveling the intricacies of electronic structures and properties of molecules. While challenges persist in qubit stability and error mitigation, continuous innovation is fostered by collaborative efforts between the quantum computing and chemistry communities. These collaborations pave the way for groundbreaking advancements in drug discovery and materials science. This research employed quantum computing simulators to investigate the potential energy surface (PES) of the H2 molecule at the CCSD/STO-3G level of theory. These simulators, leveraging qubits and sophisticated algorithms, facilitated the acquisition of detailed information regarding the electronic structure, bonding mechanisms, and spectroscopic properties of the diatomic molecules.